Organizing property: three case studies about costumary regimes and state regulations - Márquez, Raúl; Montesinos Llinares, Lidia; Sarkis Fernández, Diana (Revista de Antropología Social, 2011)
The article covers three case studies which deal with changes in different property regimes: the regularization of an informal establishment in Salvador de Bahía; the redefinition of the sharecropping relationships in the province of Banias (Syria) introduced by the regulatory law of agriculture relations (2004); and the changes in communal property regimes in Goizueta (Navarra). With the common theme of changes brought about by different state customary and historical property regimes, it can be cross observed how this intervention leads to situations and types of management based on the same structural values and principles of a genuine (neo)liberal kind, that in very different contexts produce similar effects: instability of the occupant / agricultural worker; privilege of access to the land by purchase; tendency to maximize the yield and profit, introduction into the free market circulation, etc. Likewise, the three case studies shown together allow us to explore the contradictions, oppositions and resistances that cross the establishment of the (neo)liberal dominance, showing the shared elements, as well as the characteristics that conform those other political projects that confront, in different social-historical contexts, the liberalizing process.
Keywords: Property; costumary right; communal assets; regulation; capital; work; sharecropping; dispossession; home; Navarra; Brazil; Syria